Effects of a low electron distribution cutoff on multiwavelength spectra and light curves of GRB afterglows - Petropoulou, M.; Mastichiadis, A.; Piran, T. (2011)
Aims: We investigate the behavior of the frequency-centered light curves expected within the standard model of gamma ray bursts, allowing the maximum electron energy (γmax) to be a free parameter that may take low values. Methods: We solve the spatially averaged kinetic equations that describe the simultaneous evolution of particles and photons, obtaining the multi-wavelength spectra as a function of time. From these we construct the frequency-centered light curves with an emphasis on the X-ray and optical bands. Results: We show that in cases where γmax takes low values, the produced X-ray light curves show a plateau as the synchrotron component gives its place to the synchrotron self-Compton one in the X-ray band.
Keywords: acceleration of particles; Astrophysics - High Energy Astrophysical Phenomena; gamma-rays: general; radiation mechanisms: non-thermal